A RELATIONSHIPS VARIATION A STYLE TEACHING AND A STUDIED ATTITUDE STUDENTS WITH LEARNING RESULTS (Universitas Negeri Semarang, 2017)
Variation style teaching determine response a studied attitude students in learning activities and results of the study rise .With the teacher have a variety of teaching style and attitude to study for students on subjects becoming more positive done well so you can get a good study results .Teachers need to have a variety of force in teaching and learning learning process to be active and fun , and therefore the optimum student learning .Students also study results can be influenced by a studied attitude owned students .The purpose of this research is test the whereabouts of teaching relations style teachers and a studied attitude with study results grade school students the poor semarang syafei district . This research uses the quantitative by design kolerasi .The population in research is students grade state primary school in the poor syafei district semarang totaling 126 students .Sample techniques used is a technique proportional sampling ( random sampling taking a member of the population at random and bersrata proportionally ) totaling 86 respondents .Analysis preliminary data use of normality test , linieritas and multikolinearitas .While data analysis the hypothesis final test and coefficients determination .The result showed that there is a positive and significant between style teaching teachers and attitude learn in together the student learning the grade school districts are syafei semarang indicated with large a correlation coefficient of 0,655 or 65,5 % included in the strong enough. The result of this research there was positive and significant relationship between the variations style between teach and learn in attitude together with learning outcomes students class v sdn cluster muh syafei district semarang .Advice based on the results of this study is with the variation of a style of teaching done teachers can overcome boredom on students that would give the spirit and attitude can excite students so that learning the purpose of learning desired will be achieved .